STRATEGI KOMUNIKASI PARIWISATA KULINER UNTUK PENCITRAAN MEREK DESTINASI: : (Memposisikan Mie Ayam dan Bakso sebagai Identitas Kuliner Wonogiri) - Ananda Marvian Dwi Nopiyanto (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
This study examines tourism communication strategies to promote mie ayam and bakso as culinary icons to represent Wonogiri culinary identity. Culinary tourism has become an essential component of destination branding and tourism marketing, particularly in strengthening local identity and enhancing destination competitiveness. Wonogiri is widely recognized as the origin and development center of mie ayam and bakso, yet systematic communication strategies to position these culinary products as official tourism icons remain limited. Using a qualitative descriptive approach, this research employs in-depth interviews, observation, and document analysis involving culinary entrepreneurs, tourism stakeholders, and local institutions. The study analyzes communication strategies through the dimensions of message content, communication channels, stakeholder roles, and institutional support. The findings reveal that tourism communication about mie ayam and bakso in Wonogiri remains fragmented, relying heavily on informal networks, word-of-mouth promotion, and digital media, and lacking an integrated branding strategy. This research contributes to tourism marketing and destination studies by proposing a communication strategy model that integrates culinary identity, institutional collaboration, and destination branding. The results are expected to support sustainable tourism development, strengthen local economic investment, and enhance Wonogiri’s position as a national culinary tourism destination.